Implementasi Dalam Peningkatan Kepesertaan Bpjs Ketenagakerjaan Melalui Aplikasi Jamsostek (JMO) Kcp. Pasaman Barat: Memudahkan Akses Layanan E-Government - M. Hanif Ash Shiddiqi; Syamsir Syamsir; Muhammad Akbar Rifa’i; Fadhel Fajrin Yunis; Ahmad Radifan. S; Salman Alfarisi. S; Muhammad Iqbal; Nabeel Edgar Ferdrianda (Dinasti Research, 2023)
Implementing e-government makes government work more efficient, effective, transparent and less difficult. E-government also makes communication between the government, the general public, and the private sector easier. The aim of this research is to understand the implementation of increasing BPJS Employment Membership through the KCP Jamsostek (JMO) Application. West Pasaman: Facilitating Access to E-Government Services. The research method used in this research is a qualitative deductive approach. Data collection techniques use field observation. The results of this research show that the JMO Application displays all BPJS Employment programs and benefits. Because the system is still new and in the development stage, it sometimes experiences problems. The solution provided when JMO problems occur is by adding a menu of criticism and suggestions to the JMO application, and every service officer at BPJS Employment is obliged to resolve every complaint experienced by participants regarding the JMO application. As well as evaluating the effectiveness of JMO in increasing participation. It can be seen from the report how many participants use the JMO application, both those who register as participants and those who submit benefit claims.